Language-Eloquent White Matter Pathway Tractography and the Course of Language Function in Glioma Patients - Ille, Sebastian; Engel, Lara; Kelm, Anna; Meyer, Bernhard; Krieg, Sandro M. (Frontiers in Oncology, 2018)
Object: As various recent studies show, damage to white matter pathways leads to permanent functional deficits in a high percentage of patients. Particularly the subcortical language network is complex, and its visualization has a tremendous relevance for neurosurgeons. This pilot study aims to correlate language-eloquent white matter pathways with the course of language function after the resection of left-sided perisylvian gliomas. Methods: We included 10 patients who underwent resection of highly language-eloquent high- (9 pts) and low-grade gliomas (1 pts). We performed navigated repetitive transcranial magnetic stimulation (nrTMS)-based tractography via diffusion tensor imaging fiber trackings (DTI FT) preoperatively (PRE-1), postoperatively (POST-1), and at long-term follow up or tumor recurrence (PRE-2). We separately tracked the inferior fronto-occipital fascicle (IFOF), the frontal aslant tract (FAT), and the superior longitudinal (SLF), and arcuate fascicle (AF), and correlated the amount of visualized fibers to the patients' language function at each date. Results: The changes of nrTMS-based DTI FTs of single white matter pathways correlated with the according status of language function for any of the pathways in 80% of patients and in 19 of 30 (63%) single pathway comparisons between PRE-1 and POST-1. Between POST-1 and PRE-2 the nrTMS-based DTI FTs correlated with the status of language function for any of the pathways in all patients and in 24 of 30 (80%) single pathway comparisons. Single FT results correlated with the according status of language function at POST-1 in 60, 70, and 60% of cases, and with the according status of language function at PRE-2 in 60, 90, and 90% of cases for the tracking of the IFOF, FAT, and SLF/AF, respectively. Conclusion: By the present results we were able to show that nrTMS-based DTI FT of the IFOF, FAT, and SLF/AF mainly correlates with the according status of language function preoperatively, postoperatively, and at long-term follow up after the resection of left-sided perisylvian gliomas.